Analisis Cara Komunikasi Efektif Pemilik Usaha dalam Menghadapi Turn Over Karyawan: Studi Kasus pada UMKM Pabrik Tahu Gurilem - Kintan Ayu Dalva; Fizi Fauziya (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The phenomenon of high employee turnover in the Micro, Small, and Medium Enterprises (MSMEs) sector, including at the Gurilem Tofu Factory in West Bandung Regency, is the main focus of this study. The high rate of employee turnover is considered to have a negative impact on operational efficiency, internal stability, and overall business sustainability. High turnover creates uncertainty in production rhythms, increases training costs for new employees, and decreases productivity. Based on these conditions, this study was designed to answer three main research questions: what communication patterns are implemented by business owners, to what extent is the relationship between effective communication and employee turnover, and what strategic recommendations can be implemented to improve communication patterns in order to reduce turnover rates. The purpose of this study is to identify, analyze, and evaluate the communication strategies of business owners in building more stable, harmonious, and productive work relationships. This study is based on the theory of effective communication which includes five main indicators, namely: understanding, enjoyment, influence on attitudes, improving interpersonal relationships, and encouraging action. In addition, the theory of employee turnover is used as a foundation to understand the factors causing resignation intentions, such as job dissatisfaction, lack of recognition, and limited development opportunities. The approach used in this study was descriptive qualitative, with data collection methods including in-depth interviews, direct observation, and documentation with the owner and two employees. Triangulation techniques were applied to ensure the validity and reliability of the data. The results indicate that the communication patterns implemented by the business owner largely met the criteria for effective communication, such as delivering clear instructions and using polite language. However, obstacles remained, such as a lack of firmness regarding disciplinary violations and a lack of initiative in building team cohesion, which contributed to the high turnover rate.